(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Environmental refugees are people unwilling to leave their homes and societies as a result of the effects of climate change. The other disasters are caused by anthropogenic reasons, according to the United Nations Environment Programme (UNEP). Climate change has occurred many times since the formation of the Earth billions of years ago. Human activities that produce greenhouse gases, like burning fossil fuels (coal, gas), emissions from automobiles, industries, and deforestation, contribute to global warming. Glaciers and polar ice melt as a result of rising temperature brought on by climate change. Floods and sea-level rise are outcomes of climate change. Droughts and environmental deprivation, or the conversion of fertile land into deserts, that is, desertification, are further affected by increasing temperature. For example, Rising sea levels and drought will entirely submerge the land and decrease the fertility of the land, making it hard for individuals in the region to live.